2015
DOI: 10.1177/0957650915582352
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics analysis for effect of length to diameter ratio of nozzles on performance of pre-swirl systems

Abstract: In a direct-transfer pre-swirl system, cooling air expands through stationary pre-swirl nozzles and flows through the cavity to the receiver holes located in the rotating turbine disc for blade cooling. This paper investigates the effect of the length-to-diameter ratios of pre-swirl nozzles on the performance of a direct-transfer pre-swirl system in a rotor-stator cavity. The commercial code CFX 12.1 is used to solve the Reynolds-averaged Navier-Stokes equations using the SST turbulence model. Computations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Didenko et al [18] performed a numerical study to investigate the effect of geometrical parameters in terms of the cavity width, pre-swirl nozzle location and way of air delivery on the adiabatic effectiveness, loss coefficient, and discharge coefficient. Liao et al [12] and Zhang et al [13,19] numerically studied the influences of geometrical parameters of nozzles on the adiabatic effectiveness and total pressure loss. Variations of radius ratio of pre-swirl nozzles to receiver holes, the preswirl cavity height and the pre-swirl cavity width were selected by Jarzombek et al [20] to investigate its' effects on the adiabatic effectiveness and total pressure loss.…”
Section: Introductionmentioning
confidence: 99%
“…Didenko et al [18] performed a numerical study to investigate the effect of geometrical parameters in terms of the cavity width, pre-swirl nozzle location and way of air delivery on the adiabatic effectiveness, loss coefficient, and discharge coefficient. Liao et al [12] and Zhang et al [13,19] numerically studied the influences of geometrical parameters of nozzles on the adiabatic effectiveness and total pressure loss. Variations of radius ratio of pre-swirl nozzles to receiver holes, the preswirl cavity height and the pre-swirl cavity width were selected by Jarzombek et al [20] to investigate its' effects on the adiabatic effectiveness and total pressure loss.…”
Section: Introductionmentioning
confidence: 99%
“…Using a pre-swirl in rotor-stator cavities reduces the relative total temperature of the air entering the cooling passages in the rotor. Numerous research works have been conducted on pre-swirl flow [25][26][27]. A numerical study by Liao et al [28] has revealed that the pressure ratio has an important effect on the magnitude of heat transfer coefficient and the rotating speed has a significant effect on the displacement of locations with high heat transfer coefficient.…”
mentioning
confidence: 99%